2020
DOI: 10.1177/1758835920950207
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sarcomatoid carcinoma: progress, treatment and expectations

Abstract: Pulmonary sarcomatoid carcinoma (PSC) is a unique, highly invasive pulmonary malignancy with a poor prognosis, representing 0.1–0.4% of all malignant lung tumors. Because of its highly aggressive character and propensity for frequent metastasis, PSC shows low response rates to traditional treatments such as chemotherapy, radiotherapy, and neoadjuvant therapy. In recent years, considerable progress has been made in gene sequencing, targeted therapies, and immunotherapies. One of the most promising treatment app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 89 publications
(343 reference statements)
4
74
1
Order By: Relevance
“…She was given chemotherapy with carboplatin and nab-paclitaxel. Studies have shown that EGFR mutations can be found in 8.8% (Li et al, 2020) and ALK rearrangement in 3.5% of SC of lung patients (Chen et al, 2017). Our patient reported negative for both.…”
Section: Discussionsupporting
confidence: 45%
“…She was given chemotherapy with carboplatin and nab-paclitaxel. Studies have shown that EGFR mutations can be found in 8.8% (Li et al, 2020) and ALK rearrangement in 3.5% of SC of lung patients (Chen et al, 2017). Our patient reported negative for both.…”
Section: Discussionsupporting
confidence: 45%
“…The result shows no difference in SaPC with these treatments-the first two patients received postoperative chemotherapy but relapsed in months. In terms of sarcomatoid carcinoma in other organs such as kidney (66) and lung (67), they show the similar clinicopathological characteristics as SaPC, and targeted therapy has been confirmed to be potentially beneficial. This may be the future direction of treatment for SaPC.…”
Section: Discussionmentioning
confidence: 92%
“… 6 , 26 The median survival and 5-year OS in the present study were lower than those in other real-world studies. 30 , 31 This was probably because patients with PSC in the SEER database had more aggressive grades and stages at diagnosis and had less opportunity to receive surgery (28.2%), which was absolutely associated with a poor prognosis. PSC was classified into 5 subgroups with different prognoses.…”
Section: Discussionmentioning
confidence: 99%